The power of narrative: passion and boredom in Coelho’s Adultery - Hianly Muljadi; Joanna Deborah (Universitas Islam Sultan Agung, 2023)
Adultery is a novel written by Paulo Coelho which focuses on the story of a woman named Linda, who seems to have everything in her life. However, her perfect life seems to bore her and drive her to the brink of depression. Linda then gets involved in an affair to end her boredom. At the end of the story, Linda realizes that boredom is something which will always be a part of human’s life, and mere adventures also distraction cannot abolish it. The only thing that one can do is to live their life the way it is with passion. This research analyzes the narrative techniques used in the novel based on Eastman’s theory of narrative techniques, which include point of view, time and tempo, style, and distance. This theory will measure the distance between the readers and the story/the protagonist as well as the ability of the author in delivering the message through the very techniques he has chosen. The novel has been discussed mostly in the light of the psychological condition of the protagonist or the portrayal of the female protagonist while this research focuses specifically on the narrative techniques used by Coelho in delivering his message as the author of the novel using formalism approach. At the end of this research, it can be concluded that Coelho has successfully managed to deliver his idea about boredom and passion – which are inevitable in human’s life – through the very narrative techniques he has chosen.